Marrying a widow. "El reñidero" and the filmic rewriting of theatrical successes in the new Argentinian cinema (Anclajes, 2017)
The article endeavors to analyze the process of transferring the play El reñidero in the Argentinean cinema during the sixties, seeking to establish an analytical methodology different from that implemented by the tradition of local studies on the subject. Based on a comparative review of staging decisions with a view on the role played by the contextual aspect within this process, the case study seeks to distance itself from a perspective focused exclusively on the approach of the connections that films establish with previous dramatic texts. The research aims to dismantle the various significant layers, structured in the manner of a palimpsest, that converge in the film. The essay draws attention to the way in which the notion of cinematographic “author” affects the process of transferring this work to the screen.
Keywords: René Mugica; Argentine cinema; film analysis; intermediality; performing arts